2017
DOI: 10.1002/jbm.b.33858
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of corrosion in retrieved spine implants

Abstract: Recently the use of dissimilar metals in spine instrumentation has increased, especially in the case of adult deformities, where rods made from Cobalt Chrome alloys (CoCr) are used with Titanium (Ti) screws. The use of dissimilar metals increases the risk of galvanic corrosion and patients have required revision spine surgery due to severe metallosis that may have been caused by corrosion. We aimed to assess the presence of corrosion in spine implant retrievals from constructs with two types of material combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…A retrieval study by Kirkpatrick et al [16] identified three common modes of corrosion and wear that appear to happen simultaneously in vivo; fretting wear, crevice and galvanic corrosion. In a retrieval study conducted by Villarraga et al [17] and Panagiotopoulou et al [18] wear and corrosion were the most common types of damage seen on retrieved spinal hardware and they concluded that revision spine constructs contribute to this type of damage because of the additional segments and mobile pieces added.…”
Section: In Vivo Corrosion Of Metallic Spinal Implantsmentioning
confidence: 99%
See 2 more Smart Citations
“…A retrieval study by Kirkpatrick et al [16] identified three common modes of corrosion and wear that appear to happen simultaneously in vivo; fretting wear, crevice and galvanic corrosion. In a retrieval study conducted by Villarraga et al [17] and Panagiotopoulou et al [18] wear and corrosion were the most common types of damage seen on retrieved spinal hardware and they concluded that revision spine constructs contribute to this type of damage because of the additional segments and mobile pieces added.…”
Section: In Vivo Corrosion Of Metallic Spinal Implantsmentioning
confidence: 99%
“…Several case reports have been published on revision of spine components where the reason for revisions was strongly linked with corrosion and wear of the implants [14][15][16][17][18][19][20][21][22][23]. Medical complications included unexplained pain, neurological effects, implant loosening, implant failure, swelling and metal staining of the skin.…”
Section: In Vivo Corrosion Of Metallic Spinal Implantsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, mixing dissimilar metals in spinal implants brings with it an increased risk of inducing galvanic corrosion [ 40 , 42 , 44 ]. However, biomechanical studies conducted in 0.9% sodium chloride at 37 °C and retrieval analyses of spinal instrumentation have shown no evidence of galvanic corrosion in spinal constructs made of different metals [ 42 , 45 , 46 ]. After the literature review, we compared breakdown potential to assess corrosion resistance of each discussed metal alloy ( Table 1 ).…”
Section: Physical and Mechanical Properties Of Implant Important In Lifmentioning
confidence: 99%
“…Regardless of the great progress of medical implants technology and it is suffered from a set of limitations to restrict the success rate up to some extent. Frequent issues related to orthopedic implants like corrosion, loosening of the device; due to poor mechanical strength, infection, non-integration of implant with host tissue and wearing are the prime factors of concerns [19,31,87]. The far most characteristic of an orthopedic implant is integration to host tissue to boost the success rate by resisting the colony formation of microbes and corrosion [23].…”
Section: Introductionmentioning
confidence: 99%